2015
DOI: 10.4102/sajim.v17i1.634
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge management practices at selected banks in South Africa

Abstract: Background: Effective knowledge organisations (EKO) create dynamic capabilities through the acquisition, creation, sharing and retention of knowledge. These EKOs are designed to enable an organisation to improve best practices in business. As knowledge is different from other organisational resources, decision-makers ought to understand the importance of knowledge to an organisation. In order to fully utilise knowledge-management (KM) practices and to enhance efficiency, management should appreciate and unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 26 publications
(35 reference statements)
0
14
0
Order By: Relevance
“…The study revealed that selected banks used other strategies for safeguarding knowledge such as job rotation, staff secondment and promotions. Safeguarding institutional knowledge can leverage efficiency across an organization’s services to all stakeholders through accessing the right information and converting that information into knowledge (Chigada and Ngulube, 2014). The loss of organizational knowledge through workforce attrition can be dire to the organization.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The study revealed that selected banks used other strategies for safeguarding knowledge such as job rotation, staff secondment and promotions. Safeguarding institutional knowledge can leverage efficiency across an organization’s services to all stakeholders through accessing the right information and converting that information into knowledge (Chigada and Ngulube, 2014). The loss of organizational knowledge through workforce attrition can be dire to the organization.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The quantitative research methodology was adopted because it enabled the researchers to collect large volumes of data from many research respondents; thus, culminating in rich sets of data was extracted from diverse participants (Chigada and Ngulube, 2014). Data were presented in numerical, percentages and tabular format (Babbie 2010).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to retain the knowledge of highly skilled and experienced staff, Limpopo municipalities should consider documenting and integrating knowledge into the municipalities. To achieve this, knowledge should be captured and stored in documents, databases, products and services, software and processes (Chigada & Ngulube 2015). Support from top management and political buy-in are the key factors for knowledge sharing in Limpopo municipalities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%